Frequency and duration of extreme hypoxemic and hyperoxemic episodes during manual and automatic oxygen control in preterm infants: a retrospective cohort analysis from randomized studies - Bachman, Thomas E; Onland, Wes; van Kaam, Anton H; Roubik, Karel; Hummler, Helmut D; Lal, Mithilesh; Lista, Gianluca; Fajardo, Carlos A (BMC pediatrics, 2022)
OBJECTIVE: Neonatal exposure to episodic hypoxemia and hyperoxemia is highly relevant to outcomes. Our goal was to investigate the differences in the frequency and duration of extreme low and high SpO2 episodes between automated and manual inspired oxygen control. DESIGN: Post-hoc analysis of a cohort from prospective randomized cross-over studies. SETTING: Seven tertiary care neonatal intensive care units. PATIENTS: Fifty-eight very preterm neonates (32 or less weeks PMA) receiving respiratory support and supplemental oxygen participating in an automated versus manual oxygen control cross-over trial. MAIN MEASURES: Extreme hypoxemia was defined as a SpO2 < 80%, extreme hyperoxemia as a SpO2 > 98%. Episode duration was categorized as < 5 seconds, between 5 to < 30 seconds, 30 to < 60 seconds, 60 to < 120 seconds, and 120 seconds or longer. RESULTS: The infants were of a median postmenstrual age of 29 (28-31) weeks, receiving a median FiO2 of 0.28 (0.25-0.32) with mostly receiving non-invasive respiratory support (83%). While most of the episodes were less than 30 seconds, longer episodes had a marked effect on total time exposure to extremes. The time differences in each of the three longest durations episodes (30, 60, and 120 seconds) were significantly less during automated than during manual control (p < 0.001). Nearly two-third of the reduction of total time spent at the extremes between automated and manual control (3.8 to 2.1% for < 80% SpO2 and 3.0 to 1.6% for > 98% SpO2) was seen in the episodes of at least 60 seconds. CONCLUSIONS: This study shows that the majority of episodes preterm infants spent in SpO2 extremes are of short duration regardless of manual or automated control. However, the infrequent longer episodes not only contribute the most to the total exposure, but also their reduction in frequency to the improvement associated with automated control.
Keywords: hypoxie; Hypoxia; Retrospective Studies; kojenec; Oxygen saturation; Infant; Prospective Studies; Neonatology; Oximetry; Infant, Newborn; kyslík; Hypoxemic episodes; novorozenec; retrospektivní studie; prospektivní studie; Humans; Hyperoxemia episodes; oxymetrie; Infant, Premature; Oxygen; novorozenec nedonošený; lidé